Chemoenzymatic Synthesis of 9NHAc‐GD2 Antigen to Overcome the Hydrolytic Instability of O‐Acetylated‐GD2 for Anticancer Conjugate Vaccine Development. Issue 45 (4th October 2021) - Wu, Xuanjun; Ye, Jinfeng; DeLaitsch, Andrew T.; Rashidijahanabad, Zahra; Lang, Shuyao; Kakeshpour, Tayeb; Zhao, Yuetao; Ramadan, Sherif; Saavedra, Paulo Vilar; Yuzbasiyan‐Gurkan, Vilma; Kavunja, Herbert; Cao, Hongzhi; et al.
Abstract: Ganglioside GD2 is an attractive tumor‐associated carbohydrate antigen for anti‐cancer vaccine development. However, its low immunogenicity and the significant side effects observed with anti‐GD2 antibodies present significant obstacles for vaccines. To overcome these, a new GD2 derivative bearing an N ‐acetamide (NHAc) at its non‐reducing end neuraminic acid (9NHAc‐GD2) has been designed to mimic the 9‐ O ‐acetylated‐GD2 (9OAc‐GD2), a GD2 based antigen with a restricted expression on tumor cells. 9NHAc‐GD2 was synthesized efficiently via a chemoenzymatic method and subsequently conjugated with a powerful carrier bacteriophage Qβ. Mouse immunization with the Qβ‐9NHAc‐GD2 conjugate elicited strong and long‐lasting IgG antibodies, which were highly selective toward 9NHAc‐GD2 with little cross‐recognition of GD2. Immunization of canines with Qβ‐9NHAc‐GD2 showed the construct was immunogenic in canines with little adverse effects, paving the way for future clinical translation to humans. Abstract : A potential anticancer vaccine was produced by the conjugation of bacteriophage Qβ virus‐like particle with the chemoenzymatically synthesized 9‐NHAc‐GD2 mimic of the 9‐ O ‐acetylated GD2 antigen. The conjugate produced robust and long‐lasting IgG responses in mice and canines with no observed adverse effects.